Knitted fabric and use thereof
Patent Information
- Application Number
- CN202510507775.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2026-10-23
AI Technical Summary
但是中间层采用沸水收缩率较大的全牵伸丝,虽然一定程度上降低了面料的厚度,但是导致面料过于紧实,面料的速干性有待提高
[0017]本发明通过特定的纱线选择和编织结构,获得了一种接触冷感优异、吸水速干性好、且具有骨感的防透针织面料,该针织面料适用于服用领域,特别适合用于制成高尔夫球服、POLO衫等服装。
Smart Images

Figure CN122959912A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a knitted fabric and its uses, specifically to a breathable knitted fabric with excellent cold-feel, good water absorption and quick-drying properties, and a structured feel, and its uses. Background Technology
[0002] In today's society, consumers have higher demands for the comfort and functionality of clothing. With the increasing frequency of hot and humid weather around the world, people are looking forward to the development of fabrics that are cool and comfortable to wear, and that can absorb and dry sweat quickly.
[0003] To address this, numerous studies have been conducted. For instance, patent document CN111350015A discloses a weft-knitted fabric with moisture-wicking and cooling functions. This fabric includes a fabric body, which is a composite structure composed of loops, floats, and single-sided knitting using a 1+1 rib stitch configuration. The fabric has an inner layer and an outer layer. The inner layer, which comes into contact with human skin, has a cooling and moisture-wicking layer with a flat surface composed of a front loop warp of several consecutive, incompletely ribbed knitting stitches and several front loop warps of alternating single-sided knitting stitches. The outer layer has a moisture-dissipating and heat-dissipating layer, composed of several rows of consecutive single-sided knitted front loops and several rows of rectangular concave-convex structured loops arranged alternately. This results in a weft-knitted fabric with moisture-wicking and cooling properties. However, because the fabric body uses a rib stitch structure, the fabric has high elasticity and extensibility, making it too soft and lacking in structure.
[0004] For example, patent document CN110396758A discloses a cooling circular knit fabric. This fabric is a double-sided knit, specifically disclosed as an air-layer structure comprising a surface layer, an inner layer, and a middle layer. The yarn in the middle layer is fully drawn yarn (FDY) with a boiling water shrinkage rate of 10% to 50%, resulting in a circular knit fabric that combines cooling and a sleek feel. However, while using fully drawn yarn with a high boiling water shrinkage rate in the middle layer reduces the fabric thickness to some extent, it also makes the fabric too tight, and its quick-drying properties need improvement.
[0005] For example, patent document CN111996652B discloses a moisture-wicking, quick-drying, lightweight, and breathable double-layer fabric. The fabric includes an outer layer and an inner layer. The outer layer yarn is made of 50s / 1 yarn spun from a viscose carrier and cotton fibers. The inner layer yarn is made of 75D / 72F moisture-wicking polyester. The resulting fabric has the effects of moisture-wicking, quick-drying, lightweight, and breathable, but its cold-feeling properties need to be improved. Summary of the Invention
[0006] The purpose of this invention is to provide a breathable knitted fabric with excellent cold-feel, good water absorption and quick-drying properties, and a structured feel, as well as its applications.
[0007] The technical solution of the present invention is as follows:
[0008] The present invention discloses a knitted fabric comprising a side A and a side B, wherein the yarn forming side A is yarn a, the yarn forming side B is yarn b, and the thermal conductivity of yarn b is 0.20 W / m².
[0009] (m*K) or more and its proportion in the fabric is more than 30% by weight; and in a complete fabric, the B side has at least one structure formed by a coil and an unclosed overhang, and the length of the overhang is greater than the length of the unit float.
[0010] Preferably, the incomplete filling coefficient δ of the knitted fabric is greater than 2, and the roughness SMD of the B surface is less than or equal to 5 μm.
[0011] Preferably, the monofilament fineness Da of yarn a and the monofilament fineness Db of yarn b satisfy the following relationship: 0 < Da / Db ≤ 1.
[0012] Preferably, the twist Ta of yarn a and the twist Tb of yarn b satisfy the following relationship: Ta ≥ Tb.
[0013] Preferably, the yarn a is a polyester fiber containing sulfonic acid groups.
[0014] Preferably, the inorganic particle content of the polyester fiber is 8.0 to 20.0% by weight.
[0015] Preferably, the yarn b is polyamide fiber and / or polyethylene fiber.
[0016] The present invention also discloses a garment made using the knitted fabric described above.
[0017] This invention, through specific yarn selection and weaving structure, obtains a breathable knitted fabric with excellent cold feel upon contact, good water absorption and quick-drying properties, and a structured feel. This knitted fabric is suitable for the apparel industry, and is particularly suitable for making golf apparel, polo shirts and other clothing. Attached Figure Description
[0018] Figure 1 This is a double-sided weave diagram of the double-layer structure of Embodiment 1 of the present invention.
[0019] Figure 2 This is a diagram of the single-sided weave of the double-layer structure in Embodiment 14 of the present invention.
[0020] Figure 3 This is a single-sided weave diagram of the single-layer structure of Embodiment 16 of the present invention.
[0021] Figure 4 This is a diagram of the single-sided weave of the double-layer structure of Comparative Example 3 of the present invention. Detailed Implementation
[0022] The knitted fabric of this invention comprises a side A and a side B. The yarn forming side A is yarn a, and the yarn forming side B is yarn b. Yarn b has a thermal conductivity of 0.20 W / (m*K) or higher, and yarn b accounts for 30% by weight or more of the fabric. Thermal conductivity is an essential indicator of heat transfer. When the thickness of the material is 1 m and the temperature difference between its two ends is 1 °C, the thermal conductivity of the material is measured by the amount of heat transferred through the 1 m thick material in one second. 2 The amount of heat conducted by a material is called its thermal conductivity. A higher thermal conductivity value indicates that the material conducts more heat per unit time. In this invention, the proportion of yarn b with a thermal conductivity of 0.20 W / (m*K) or higher in the fabric is 30% by weight or more, preferably 40% by weight or more, and more preferably 50% by weight or more. A higher proportion of high thermal conductivity yarn in the fabric results in a better cooling effect upon contact. The knitted fabric of this invention allows for instantaneous heat loss from the skin surface upon contact, thereby producing a noticeable cooling sensation.
[0023] In the knitted fabric of the present invention, in a complete weave, side B has at least one structure formed by a loop and an unclosed overhang, and the length of the overhang is greater than the length of a unit float. The knitted fabric of the present invention can be a double-sided or single-sided weave; considering the need to obtain a knitted fabric with both water absorption and quick-drying properties as well as a cooling effect, a double-sided or single-sided weave with a double-layer structure is preferred.
[0024] When the fabric is a double-layered, double-sided weave, yarn a forms an unclosed overhang, which hangs below the stitched arc of the loop formed by yarn b. That is, yarn a on surface A, suspended in an overhang state below the stitched arc of the loop formed by yarn b on surface B, experiences tensile force due to this structure, resulting in a mesh structure on surface A. When the fabric is a double-layered, single-sided weave, all loops and the unclosed overhang are woven together by yarns a and b respectively. The unclosed overhang hangs above the stitched arc of the loops, increasing the loop height and creating a mesh structure on surface A.
[0025] When the fabric has a double-layer construction, it is preferable that the unclosed overhanging arc (mesh structure) formed by yarn a is not exposed on the B side of the fabric. That is, the B side is entirely composed of loops formed by yarn b, which has a large contact area with the skin and improves the cooling sensation. Moreover, the mesh structure formed on the A side can increase the flow area between moisture and air on the B side, resulting in faster moisture evaporation and giving the fabric excellent quick-drying properties. In addition, the mesh structure on the A side, composed of two yarns, can also give the fabric a certain texture, improving its softness and enhancing its structure.
[0026] Preferably, in this invention, the incomplete filling coefficient δ of the knitted fabric is greater than 2, and the surface roughness SMD of surface B is less than or equal to 5 μm. A larger incomplete filling coefficient δ results in a more sparse fabric and better quick-drying properties. However, a larger incomplete filling coefficient also reduces the contact area between the fabric and the skin, leading to a decrease in the cooling sensation. Similarly, surface roughness SMD is a parameter characterizing the smoothness of the fabric surface. A smaller roughness results in a smoother fabric, increasing the contact area with the skin and improving the cooling effect. However, a larger contact area also tends to decrease the absorbency and quick-drying properties.
[0027] If the incomplete filling coefficient δ of the knitted fabric is greater than 2, but the surface roughness SMD of side B is greater than 5 μm, the smoothness of side B decreases, the contact area between the fabric and the skin becomes smaller, and the cooling effect of the fabric tends to decrease; therefore, this is not preferred. If the surface roughness SMD is less than or equal to 5 μm, but the incomplete filling coefficient δ is less than or equal to 2, the fabric is smooth and dense, but its water absorption and quick-drying properties tend to decrease; therefore, this is not preferred. When the incomplete filling coefficient δ of the knitted fabric is greater than 2, and the surface roughness SMD of side B is less than or equal to 5 μm, the knitted fabric has both excellent cooling effect and water absorption and quick-drying properties; therefore, this is preferred.
[0028] Preferably, the monofilament fineness Da of yarn a and the monofilament fineness Db of yarn b satisfy the following relationship: 0 < Da / Db ≤ 1, more preferably 0 < Da / Db < 1. This is because, within this range, a capillary effect can be formed between the fibers on the A and B sides of the fabric, meaning that yarn a can quickly absorb moisture from yarn b, and then the moisture is diffused and evaporated by yarn a, thus improving the fabric's absorbency and quick-drying properties.
[0029] Preferably, in this invention, the twist Ta of yarn a and the twist Tb of yarn b satisfy the following relationship: Ta ≥ Tb, more preferably Ta > Tb. Within this range, the mesh structure of surface A is stable, the flatness of surface B is good, the knitted fabric has good water absorption and quick-drying properties and a cool-to-the-touch effect, and the fabric has a good structure. Specifically, the twist of yarn a is preferably 400-600 twists / meter (hereinafter referred to as T / m), more preferably 400-500 T / m. Yarn a has a certain twist, the cohesion between fibers is large, and the bundled properties are strong. The surface A formed by it not only has a stable mesh structure, which reduces the obstruction of the fabric's water vapor dissipation channels, which is conducive to the evaporation of moisture into the air, thus improving the quick-drying properties of the fabric, but also improves the fabric's structure. The twist of yarn b is preferably below 400 T / m, more preferably 0 T / m. Yarn b is a weakly twisted or untwisted yarn. The single fibers of the yarn are in a straight state, and the resulting B surface is smoother. This not only improves the fabric's coolness to the touch, but the smooth surface formed by the straight fibers also provides better water absorption and wicking properties when in contact with the skin, thus increasing the fabric's water absorption and quick-drying properties.
[0030] Preferably, in this invention, yarn a is polyester fiber, such as PET fiber, and more preferably polyester fiber containing sulfonic acid groups (cationic dyeable polyester fiber, abbreviated as CDP fiber). Fabrics made from it have good quick-drying properties and high dye saturation.
[0031] Preferably, in this invention, yarn a is a polyester fiber containing sulfonic acid groups, and the inorganic particle content of this polyester fiber is 8.0-20.0% by weight. Inorganic particles scatter incident light, which can hinder light transmission and reduce light transmittance. When inorganic particles are added to the fiber, the reflective interface inside the fiber can be increased, thereby giving the fabric an anti-seepage effect. Here, the anti-seepage effect means that it is difficult to see the color of the inner layer on side A where yarn a is located, avoiding the embarrassing situation of physical seepage during the wearing process. When the inorganic particle content in yarn a is above 8.0% by weight, the anti-seepage effect of the fabric is better; however, when the inorganic particle content in yarn a is greater than 20.0% by weight, there are problems such as poor engineering passability and reduced yarn spinnability.
[0032] Preferably, in this invention, the yarn b is polyamide fiber (NY fiber) and / or polyethylene fiber (PE fiber). More preferably, yarn b is polyamide fiber containing cooling particles and / or polyethylene fiber containing cooling particles, wherein the raw material of the cooling particles is not particularly limited and can be jade particles, silicon carbide particles, barium sulfate particles, etc. Further preferably, yarn b is a bio-based yarn containing inorganic cooling particles, considering that bio-based yarns have higher moisture absorption, resulting in a fabric with superior contact cooling sensation.
[0033] In this invention, the fiber morphology of yarn a is preferably drawn-textured yarn (DTY). The fiber morphology of yarn b is preferably fully drawn yarn (FDY). This is because the single fibers of FDY are straight, which can make the roughness of the B-side less, the fabric smoother when in contact with the skin, and the coolness of the fabric is better.
[0034] The fineness of the yarns forming the knitted fabric of the present invention is not particularly limited. Preferably, the total fineness of yarn a is less than that of yarn b. More preferably, the total fineness of yarn a is 30 to 100 denier (hereinafter referred to as D), and even more preferably 50D to 80D; the total fineness of yarn b is more preferably 40D to 150D, and even more preferably 80D to 100D.
[0035] In this invention, by configuring yarns with different functions in different positions, the A side and B side of the fabric can have different functionalities. For example, by configuring polyester yarn a with an inorganic particle content of 8.0 to 20.0% by weight in the A side and yarn b with a thermal conductivity of 0.20 W / (m*K) or higher in the B side, a water-absorbing and quick-drying fabric with good impermeability in the A side and good cold contact feel in the B side can be obtained.
[0036] Garments made using the knitted fabric of this invention. This knitted fabric is suitable for apparel, and is particularly suitable for making golf apparel, polo shirts, and other garments.
[0037] The preparation method of the knitted fabric of the present invention is not particularly limited. The resin finishing process is preferably water-absorbing resin finishing. The resin can be polyester resin, acrylic resin, etc., and the processing method can be bath finishing or padding finishing.
[0038] The present invention will be further described below with reference to embodiments and comparative examples.
[0039] The testing methods for each parameter involved in this invention are as follows:
[0040] (1) Determination of the thermal conductivity of yarn b
[0041] ① Cut a 20cm×20cm flat and wrinkle-free piece of fabric to be tested as a sample, remove one complete fabric cycle, separate the removed yarns and place them separately, repeat the disassembly of multiple unit cycles until the total mass of each yarn is more than 3g, and then test it for later use.
[0042] ② Melting Sample Preparation: Take 3g (±0.1g) of the yarn to be tested and place it in a special standard aluminum tray that matches the size of the sample carrier stage of the laser thermal conductivity analyzer (manufacturer: Netzsch Instruments GmbH, Germany, equipment model: LFA-427). After the heating stage is heated to about 360℃, place the aluminum tray on the heating stage to melt the yarn.
[0043] ③ When the yarn sample to be tested in the aluminum tray is in a molten state, place the aluminum tray containing the molten liquid in the specified position of the sample preparation machine and press it into a cake-shaped solid with a diameter of 12.7 mm and a thickness of more than 0.5 mm;
[0044] ④ Connect the power supply, turn on the switches of each instrument and computer from left to right, and check whether the indicator lights are lit normally.
[0045] ⑤ Raise the furnace body, remove the sample carrier, load the sample, lower the furnace body and tighten the furnace switch, and pour liquid nitrogen from the top.
[0046] ⑥ Turn on the vacuum pump to evacuate the gas. Stop evacuating when the pressure gauge pointer reaches -1.0. Turn on the gas flow meter to purge nitrogen. Stop purging nitrogen when the pressure gauge pointer returns to 0. Repeat 2-3 times.
[0047] ⑦ Set the gas flow meter to 70-80 and open the exhaust valve;
[0048] ⑧ Click the flash button in the software to confirm whether the sample is loaded and whether the instrument is stable;
[0049] 9. Set the measurement parameters and click the "Start Measurement" button in the software;
[0050] ⑩ Repeat the above steps three times. Yarn with a result greater than 0.20W / m*K is yarn b.
[0051] After all samples have been tested, turn off all instruments from right to left.
[0052] (2) The proportion of yarn b in the fabric (by weight %)
[0053] To ensure the accuracy of the experimental data, all samples used in the following tests were conditioned for more than 12 hours in a constant temperature and humidity environment (65±4%RH, 20.0±2℃) before testing.
[0054] The specific steps of the test are as follows:
[0055] A. Measurement of the length L of 100 coils
[0056] ① Cut three flat, wrinkle-free test pieces that have completed at least five full cycles as samples;
[0057] ② Take one sample, designating the side containing yarn b as side B and the other side as side A. Mark the width of 100 loops on both sides of the fabric and disassemble the sample;
[0058] ③ Fix one end of yarn a and yarn b respectively and let them hang down. Apply a load of 0.1 g / D (filament) or 0.5 cN / tex (staple fiber) to the other end. After measuring for 30 seconds, mark the length of 100 loops of yarn a and yarn b respectively, and record them as La and Lb, in mm.
[0059] B. Measurement of yarn count
[0060] Under the microscope, count the number of yarns a and b in one unit cycle, and record them as Na and Nb respectively.
[0061] C. Calculation
[0062] The calculation is performed using the formula [Lb*Nb / (La*Na+Lb*Nb)]*100%.
[0063] Repeat the above steps to measure the remaining two samples, and take the average of the three results as the final result, in units of weight.
[0064] (3) Incomplete filling coefficient δ
[0065] The unfilled coefficient δ = loop length L0 (mm) / yarn diameter d (mm). The larger the value, the sparser the fabric.
[0066] The measurement of coil length is performed by referring to the test method “(2)A. Measurement of the length L of 100 coils”, and then the obtained value is divided by 100 to obtain the coil length of one coil, which is denoted as L0.
[0067] The specific method for measuring yarn diameter d is as follows:
[0068] ① Cut three sample pieces of fabric, each 1.0 cm long and 0.5 cm wide, along the weft direction of the fabric;
[0069] ② Take one of the sample fabrics and attach any one of the two cut surfaces along the weft direction to the sample stage (a sample stage for gold sputtering of an electron microscope).
[0070] ③ Using a Thermo Scientific scanning electron microscope (model: Apreo 2C), photograph the cross-section of the knitted fabric along another section in the weft direction. Specifically: adjust the electron microscope to 1000x magnification, focus on the observation area, and take a clear photograph to obtain a photograph of the fabric cross-section;
[0071] ④ On the above cross-sectional photographs, select 10 single fiber cross-sections with regular shapes, use the ruler on the electron microscope to measure the diameter of the yarn cross-section, and save the image with the ruler data.
[0072] ⑤ Calculate the average of the above 10 data points, which is the diameter of a single yarn fiber on the fabric, in μm;
[0073] ⑥ Count the total F-number of the yarn to be tested on the photograph;
[0074] ⑦ Multiply the single fiber diameter obtained in ⑤ by the yarn F number obtained in ⑥, and denote the product as the yarn diameter d.
[0075] C. Calculation
[0076] δ=L0 / d
[0077] The results are calculated using the above formula. The above steps are repeated to measure the remaining two samples, and the average of the three results is taken as the final result.
[0078] (4) Measurement of surface roughness (SMD)
[0079] According to the KES FB4 (surface properties) test, the smaller the value, the less unevenness and the higher the surface smoothness. The specific test results are as follows:
[0080] ① All samples used in the test were conditioned for more than 12 hours in a constant temperature and humidity environment (65±4%RH, 20.0±2℃);
[0081] ② Cut three flat, wrinkle-free specimens measuring 20cm x 20cm as the test samples;
[0082] ③ Apply experimental tape to the reverse side of the sample to be tested (to prevent slippage during testing);
[0083] ④ Place the test sample cloth with the tape on it facing up, and apply a 4Kg load to the test sample for more than 12 hours (to ensure that the fabric and tape are just in contact, and at the same time flatten the fabric).
[0084] ⑤ Remove the load from the sample cloth and release it for more than 12 hours;
[0085] ⑥ The equipment needs to be preheated for 15 minutes before testing (Manufacturer: KES Style Tester FB4 (Friction and Surface Roughness Tester), Equipment Model: Japan KATO TECH). The instrument environment should be kept at a constant temperature and humidity. Excessively high or low temperatures will affect operation. The instrument should be used below 35℃. Power-on sequence: Amplifiers → Controller → Other external devices (such as printers) → Computer; Power-off sequence is the reverse of power-on sequence.
[0086] ① Equipment adjustment and zero-point confirmation;
[0087] ② Add a 200g load, clamp one end of the sample to be tested with the clamp, and fix the other end to the fixed position of the sample loading position on the equipment. After setting up the equipment, start the test.
[0088] ③ Use the computer connected to the device to open the computer program KES CALC to read and statistically analyze data;
[0089] ④ Repeat the above operation 2 times, and take the average of the data obtained from the 3 tests as the desired result.
[0090] (5) Monofilament fineness of yarn
[0091] The test was conducted according to the GB / T 14335-2008 method, which is the mid-section weighing method of A-bundle fibers.
[0092] (6) Yarn twist
[0093] The filament yarn was tested according to GB / T 14345-2008.
[0094] The staple fiber yarn was tested according to GB / T 2543.1-2015 (direct counting method).
[0095] (7) Determination of inorganic particle content in yarn a
[0096] ① Cut a flat, wrinkle-free sample piece approximately 15cm x 15cm and remove the yarn to be tested from the fabric.
[0097] ② Melting sample preparation: Take 4g (±0.1g) of the yarn to be tested and place it in a special standard aluminum tray that matches the size of the sample stage of the X-ray fluorescence spectrometer (manufacturer: Rigaku, model: ZSX PrimusⅢ+). After the heating stage is heated to about 360℃, place the aluminum tray on the heating stage to melt the yarn.
[0098] ③ When the yarn sample to be tested in the aluminum tray is in a molten state, place the aluminum tray containing the molten liquid in the designated position of the sample preparation machine and press it into a cake-shaped solid.
[0099] ④ Place the aluminum disk containing the cake-shaped solid sample into the designated position on the testing instrument, and determine the content of the metal elements by X-ray fluorescence spectrometry;
[0100] The content of inorganic particles in yarn a can be calculated by using the molecular formula.
[0101] (8) Identification of fiber raw materials
[0102] Identification was performed according to FZ / T 01057-2007, the test method for identifying textile fibers.
[0103] (9) Cold sensation upon contact
[0104] According to GB / T 35263-2017 standard, the temperature difference (△T) is 15℃ for testing.
[0105] (10) Water droplet diffusion time
[0106] Tested according to GB / T 21655.1-2023.
[0107] The smaller the value, the better the absorbency.
[0108] (11) Drying rate
[0109] Tested according to GB / T 21655.1-2023.
[0110] The higher the value, the faster the drying rate, indicating better quick-drying properties.
[0111] (12) Permeability
[0112] Tests were conducted according to JIS L 1923:20.017 (B-method instrumentation).
[0113] The higher the value, the better the waterproofing.
[0114] The present invention will be further described below through examples and comparative examples.
[0115] Example 1
[0116] 35D / 36f CDP DTY yarn (16.0 wt% titanium dioxide inorganic particles, twist 600 T / m) was selected as yarn a, and 80D / 68f PE FDY yarn (twist 0 T / m) was selected as yarn b. On a 32G double-sided circular knitting machine, according to the attached... Figure 1 The fabric is woven according to the shown structure, with yarn b configured in rows 1, 2, 4, and 5, and yarn a configured in rows 3 and 6. The weaving length of the yarns is adjusted so that yarn a is not visible on side B, and yarn b accounts for 80% by weight of the fabric, resulting in a greige fabric. The greige fabric is then subjected to scouring (scouring agent 1g / L, 90℃*20min), dyeing (cationic dye 3% owf, 110℃*30min), in-bath water absorption (dyeing in the same bath, polyester hydrophilic resin 5g / L, 110℃*30min), and finishing and setting (105℃*25m / min), resulting in a basis weight of 175g / m². 2 The double-knitted fabric has specific parameters shown in Table 1.
[0117] Example 2
[0118] A 70D / 72f CDP DTY yarn (16.0% by weight of titanium dioxide inorganic particles, twist of 600T / m) was selected as yarn a, and a 70D / 48f PE FDY yarn (twist of 0T / m) was selected as yarn b. The weaving length of the yarns was adjusted so that yarn b accounted for 60% by weight of the fabric, with the rest being the same as in Example 1. The resulting fabric weight was 170 g / m². 2 The double-knitted fabric has specific parameters shown in Table 1.
[0119] Example 3
[0120] 80D / 72f CDP DTY yarn (16.0% by weight of titanium dioxide inorganic particles, twist of 600T / m) was selected as yarn a, and 40D / 34f PE FDY yarn (twist of 0T / m) was selected as yarn b. The weaving length of the yarns was adjusted so that yarn b accounted for 30% by weight in the fabric. The rest was the same as in Example 1, resulting in a basis weight of 150g / m². 2 The double-knitted fabric has specific parameters shown in Table 1.
[0121] Example 4
[0122] 80D / 68f NY FDY (twist of 0T / m, with added cooling particles) was selected as yarn b. The weaving length was adjusted so that yarn b accounted for 60% by weight in the fabric. Finishing and shaping were carried out (160℃*25m / min), and the rest was the same as in Example 2, resulting in a basis weight of 175g / m². 2 The double-knitted fabric has specific parameters shown in Table 1.
[0123] Example 5
[0124] 70D / 72f CDP DTY (8.0 wt% titanium dioxide inorganic particles, twist of 600 T / m) was selected as yarn a, and the rest was the same as in Example 4, resulting in a basis weight of 170 g / m². 2 The double-knitted fabric has specific parameters shown in Table 1.
[0125] Example 6
[0126] 70D / 72f CDP DTY (12.0 wt% titanium dioxide inorganic particles, twist of 600 T / m) was selected as yarn a, and the rest was the same as in Example 4, resulting in a basis weight of 170 g / m². 2 The double-knitted fabric has specific parameters shown in Table 1.
[0127] Example 7
[0128] 50D / 36f PET DTY (16.0 wt% titanium dioxide inorganic particles, twist 600 T / m) was selected as yarn a, and 70D / 48f NY FDY yarn (twist 0 T / m) was selected as yarn b. The unit weave cycle consists of 8 loops, with loops 1 to 8 being respectively... Figure 1 The first, third, second, third, fourth, sixth, fifth, and sixth threads are woven in an 8-thread cyclical pattern. Threads 1, 3, 5, and 7 are configured with yarn b, and threads 2, 4, 6, and 8 are configured with yarn a. The yarn lengths are adjusted to obtain the greige fabric. The rest is the same as in Example 4, resulting in a fabric weight of 169 g / m². 2 The double-knitted fabric has specific parameters shown in Table 1.
[0129] Example 8
[0130] 70D / 72f CDP DTY (7.0 wt% titanium dioxide inorganic particles, twist of 600 T / m) was selected as yarn a, and the rest was the same as in Example 4, resulting in a basis weight of 175 g / m². 2 The double-knitted fabric has specific parameters shown in Table 1.
[0131] Example 9
[0132] 70D / 72f PET DTY (0.25% by weight of titanium dioxide inorganic particles, twist of 600T / m) was selected as yarn a, and the rest was the same as in Example 4, resulting in a basis weight of 175g / m². 2 The double-knitted fabric has specific parameters shown in Table 1.
[0133] Example 10
[0134] 70D / 72f CDP DTY (16.0 wt% titanium dioxide inorganic particles, 0 T / m twist) was selected as yarn a, and 70D / 48F NY FDY (300 T / m twist, no added cooling particles) was selected as yarn b. The rest was the same as in Example 4, resulting in a basis weight of 175 g / m². 2 The double-knitted fabric has specific parameters shown in Table 1.
[0135] Example 11
[0136] 70D / 36f CDP DTY (16.0 wt% titanium dioxide inorganic particles, twist of 600 T / m) was selected as yarn a, and 70D / 48f NY FDY (twist of 0 T / m) was selected as yarn b. The rest was the same as in Example 4, resulting in a basis weight of 175 g / m². 2 The double-knitted fabric has specific parameters shown in Table 2.
[0137] Example 12
[0138] 50D / 48f CDP DTY (16.0 wt% titanium dioxide inorganic particles, twist 600 T / m) was selected as yarn a, and 50D / 42f NY FDY (0 T / m twist) was selected as yarn b. The rest was the same as in Example 4, except that the yarn length was adjusted so that yarn b accounted for 60 wt% of the fabric, resulting in the grey fabric. The rest was the same as in Example 4, yielding a basis weight of 154 g / m². 2 The double-knitted fabric has specific parameters shown in Table 2.
[0139] Example 13
[0140] After adjusting the overfeed parameters for the final shaping and processing, the rest is the same as in Example 4, resulting in a basis weight of 177 g / m³. 2 The double-knitted fabric has specific parameters shown in Table 2.
[0141] Example 14
[0142] 75D / 72f CDP DTY (16.0 wt% titanium dioxide inorganic particles, twist 600 T / m) was selected as yarn a, and 80D / 68f NY FDY (twist 0 T / m) was selected as yarn b. The yarns were then used on a 32G single-sided circular knitting machine according to the attached... Figure 2The weaving process is as shown. Yarns a and b are simultaneously configured in the first, second, and third threads. Yarns b and a are fed in at an alternating top-bottom position. The weaving length of the yarns is adjusted to ensure that yarn b is above yarn a, so that yarn a is not visible on side B. Yarn b accounts for 60% by weight of the fabric, resulting in a grey fabric. The rest is the same as in Example 4, yielding a basis weight of 185 g / m². 2 The single-sided knitted fabric has specific parameters shown in Table 2.
[0143] Example 15
[0144] 80D / 68f CDP DTY (16.0 wt% titanium dioxide inorganic particles, twist 600 T / m) was selected as yarn a, and 80D / 68f bio-based NY FDY (twist 0 T / m) was selected as yarn b. The rest was the same as in Example 14, resulting in a basis weight of 188 g / m of the present invention. 2 The single-sided knitted fabric has specific parameters shown in Table 2.
[0145] Example 16
[0146] A 75D / 72f CDP DTY yarn (16.0 wt% titanium dioxide inorganic particles, twist 600 T / m) with a thermal conductivity of 0.22 W / (m*K) was selected as yarn b, and the yarn was manufactured according to the attached... Figure 3 The fabric is woven according to the shown structure, with yarn b configured in the first, second, and third rows (i.e., yarn b and yarn a are the same yarn). Yarn b accounts for 100% by weight in the fabric, and the rest is the same as in Example 10, resulting in a basis weight of 180 g / m². 2 The single-sided knitted fabric has specific parameters shown in Table 2.
[0147] Example 17
[0148] 75D / 72f PET DTY (16.0 wt% titanium dioxide inorganic particles, twist 600 T / m) was selected as yarn a, and 80D / 68f NY FDY (twist 0 T / m) was selected as yarn b. The unit weave cycle consists of 4 loops, with loops 1 to 4 being respectively... Figure 2 The first, second, third, and fourth rows are woven in a four-row, one-cycle pattern. Yarns a and b are simultaneously placed in rows 1, 2, 3, and 4, with yarns b and a fed in an up-down, one-up-down position, to obtain the grey fabric. The rest is the same as in Example 10, resulting in a fabric weight of 185 g / m². 2 The single-sided knitted fabric has specific parameters shown in Table 2.
[0149] The garments were made using Examples 1 to 17.
[0150] Comparative Example 1
[0151] Adjust the yarn weave length and yarn configuration so that yarn a is not visible on side B, and yarn b accounts for 20% by weight of the fabric. The rest is the same as in Example 4, resulting in a basis weight of 170 g / m². 2 The double-knitted fabric has specific parameters shown in Table 2.
[0152] Comparative Example 2
[0153] A 75D / 72f PET DTY with a thermal conductivity of 0.15W / (m*K) (16.0 wt% titanium dioxide inorganic particles, twist of 600T / m) was selected as yarn b. The rest of the process was the same as in Example 4, resulting in a basis weight of 170g / m². 2 The double-knitted fabric has specific parameters shown in Table 2.
[0154] Comparative Example 3
[0155] Adopting attachment Figure 4 The weave is performed according to the shown structure, with yarns a and b simultaneously configured in rows 1, 2, 3, and 4, and the rest is the same as in Example 14, resulting in a weight of 190 g / m². 2 The single-sided knitted fabric has specific parameters shown in Table 2.
[0156]
[0157]
[0158] According to Tables 1 and 2,
[0159] (1) As can be seen from Examples 8 and 4, under the same conditions, the knitted fabric with an inorganic particle content of 7.0% by weight of yarn a is not as good as the knitted fabric with an inorganic particle content of 16.0% by weight of yarn a. The contact coolness and water absorption and quick-drying performance of the two are comparable.
[0160] (2) As can be seen from Examples 10 and 4, under the same conditions, the knitted fabric with yarn a twist less than yarn b and yarn a twist greater than yarn b has better contact cooling and quick-drying properties than the knitted fabric with yarn a twist greater than yarn b. The two fabrics have comparable anti-permeability.
[0161] (3) As can be seen from Examples 11 and 4, under the same conditions, the knitted fabric with Da / Db greater than 1 has better water absorption and quick-drying properties than the knitted fabric with Da / Db less than 1, while the two have comparable anti-permeability and cold-feel properties.
[0162] (4) As can be seen from Examples 12 and 4, under the same conditions, the knitted fabric with an unfilled coefficient δ of 2.0 has better water absorption and quick-drying performance than the knitted fabric with an unfilled coefficient δ of 2.8. The two fabrics have similar anti-permeability and cold-feel performance.
[0163] (5) As can be seen from Examples 13 and 4, under the same conditions, the knitted fabric with a surface roughness SMD of 5.2 on the B side has a lower contact cooling performance than the knitted fabric with a surface roughness SMD of 1.2 on the B side. The two fabrics have comparable anti-permeability and water absorption and quick-drying performance.
[0164] (6) As can be seen from Comparative Example 1 and Example 4, under the same conditions, the knitted fabric with a yarn b ratio of 20% by weight has a less cold feel when in contact than the knitted fabric with a yarn b ratio of 60% by weight. The two fabrics have comparable anti-permeability and water absorption and quick-drying properties.
[0165] (7) As can be seen from Comparative Example 2 and Example 4, under the same conditions, the knitted fabric with a thermal conductivity of 0.15W / (m*K) for yarn b is less cold to the touch than the knitted fabric with a thermal conductivity of 0.32W / (m*K) for yarn b. The two fabrics have similar anti-permeability and water absorption and quick-drying properties.
[0166] (8) As can be seen from Comparative Example 3 and Example 14, under the same conditions, the knitted fabric without the structure formed by the coil and the unclosed overhang has better water absorption and quick-drying performance than the knitted fabric with the structure formed by the coil and the unclosed overhang. The contact cooling sensation and anti-permeability effect of the two are comparable.
Claims
1. A knitted fabric comprising side A and side B, characterized in that: The yarn forming side A is yarn a, and the yarn forming side B is yarn b. Yarn b has a thermal conductivity of 0.20 W / (m*K) or higher and its proportion in the fabric is 30% by weight or higher. In a complete weave, side B has at least one structure formed by a loop and an unclosed suspension arc, and the length of the suspension arc is greater than the length of a unit float.
2. The knitted fabric according to claim 1, characterized in that: The incomplete filling coefficient δ of the knitted fabric is greater than 2, and the roughness SMD of the B surface is less than or equal to 5 μm.
3. The knitted fabric according to claim 1 or 2, characterized in that: The monofilament fineness Da of yarn a and the monofilament fineness Db of yarn b satisfy the following relationship: 0 < Da / Db ≤ 1.
4. The knitted fabric according to claim 1 or 2, characterized in that: The twist Ta of yarn a and the twist Tb of yarn b satisfy the following relationship: Ta ≥ Tb.
5. The knitted fabric according to claim 1 or 2, characterized in that: The yarn a is a polyester fiber containing sulfonic acid groups.
6. The knitted fabric according to claim 5, characterized in that: The inorganic particle content of the polyester fiber is 8.0 to 20.0% by weight.
7. The knitted fabric according to claim 1 or 2, characterized in that: The yarn b is polyamide fiber and / or polyethylene fiber.
8. Garments made using the knitted fabric according to any one of claims 1 to 7.
Citation Information
Patent Citations
Cool circularly-knitted fabric
CN110396758A
Weft-knitted fabric with moisture absorption and cooling functions
CN111350015A
A moisture-wicking, quick-drying, lightweight, and breathable double-layer fabric
CN111996652B